Penerapan Teknologi Tepat Guna (Penanaman Hidroponik menggunakan Media Tanam) pada Komunitas PKK di Bluru Kidul Sidoarjo - Aulia Najmi Laily; Amelia Novita Kartikasari; M. Alghaniy Brilliantsyah; Nila Nurlaily Fadhiyah; Shava Raysa Mirza; Romeo Putra Dirama; Eka Adinda Nawang Tirta; Abiyyu Fawwaz Abrizam; Muhammad Raka Wibowo; Binti Azizatun Nafi’ah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The development of agricultural technology can help communities to establish food security. This can be expected to help fulfill food as one of the basic needs of human life which is increasing. Because humans are wasteful, there is a need for agricultural technology that is easy to apply to the home, cheap to manufacture, and environmentally friendly. Therefore, we have a solution: create hydroponics using plastic bottles of trash media. The method used is socialization using PowerPoint media which contains knowledge about farming using a hydroponic and zero-waste system. With this activity, it is hoped that the community will utilize the knowledge about growing hydroponically by utilizing plastic waste. The results of this planting can be used for food security and also plastic waste processing in Blurukidul village.